Challenges and Motivations for the Development of an Intrapreneurship Initiative in a Public University - Souza, Carla Patricia da Silva; Takahashi, Adriana Roseli Wünsch (Revista de Administração da UFSM, 2017)
The aim of this study is to analyze the challenges and motivations that permeate the intrapreneurial initiatives in the Brazilian public sector. The conceptual contribution is the alignment of intrapreneurship and motivation for public service and a focus on the practices of this sector. The study uses a qualitative approach, and the method is a case study conducted at a Brazilian public university that offers a post-graduate program in Bioinformatics. The working relationships between the public university and the teaching staff show a propensity towards civic virtues, given that there are no extraneous rewards or increased remuneration for those involved in intrapreneurship initiatives. Finally, in the case in question, the actors showed strong internal motivation, characterized by an intrapreneurial initiative that sought to provide better services and generate value for society.